Aerobic composting of chicken manure with penicillin G: Community classification and quorum sensing mediating its contribution to humification. (May 2022) - Kang, Jie; Yin, Ziliang; Pei, Fangyi; Ye, Zeming; Song, Gang; Ling, Hongzhi; Gao, Dongni; Jiang, Xueyong; Zhang, Chi; Ge, Jingping
Graphical abstract: Highlights: Penicillin G reduced humification. Cooperation among bacterial communities to regulate humification. Quorum sensing mediated cooperation between bacterial communities. Quorum sensing regulated humification. Abstract: Chicken manure containing antibiotics is a hazardous biological waste. The purpose of our study was to investigate how different concentrations of penicillin G alter the bacterial community to affect humification during aerobic composting of chicken manure. The effect of quorum sensing on the bacterial community was also evaluated. Penicillin G mainly affects low fold changes (within 4) for low-abundance (within 200) microbial genera. We found that the bacterial community cooperated to regulate humus and humic acid synthesis. The microbial genera that make up the bacterial community are different, but each bacterial community may have the same ecological function. Quorum sensing affects humic acid synthesis by regulating carbohydrate metabolism and amino acid metabolism in bacterial communities through mechanisms such as the pentose phosphate pathway and the shikimate pathway. This work presents an understanding of the impact of quorum sensing on the collaboration between bacterial communities during composting.